(untitled) (World Bulletin of Public Health, 2023)
The aim of the current study is to evaluate radon levels in patients with renal failure in serum and urine samples in Najaf province. and compare the measurements with those of healthy individuals. Contrary to results measured in healthy individuals, radon (222Rn), which is a common emitter of alpha particles. Kidney diseases, especially kidney failure, are becoming more common in Najaf Governorate. Especially after the Gulf War in 1991 and the events of 2003 and what followed. It is important to know the measurement of radon concentration in the serum and urine of patients with renal failure. The relationship between these cases and the effects of successive wars. The CR-39 detector was used for this investigation to measure radon-emitting alpha particles. Samples were collected from sick and healthy (20) patients, divided into (10) males and (10) females. (20) healthy individuals were collected, divided into (10) males and (10) females. These samples were obtained from Al-Sadr Teaching Hospital in Al-Najaf. Pathway intensities were calculated using the TASLIMAGE system after the 90-day exposure period. The results showed that patients with renal failure had an average concentration of radon in their serum 8.709 ± 7.639 Bq / m3, and in urine 6.4523 ± 0.77 Bq / m3. In addition to the above, people with kidney failure have much higher radon concentrations than healthy people. The results also revealed that all measured radon concentrations (both in patients and healthy subjects) were below recommended levels. Within the permissible limit (200Bq/m3) set by the International Atomic Energy Agency (IAEA) and the International Committee for Radiation Protection (ICRP), respectively